PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DALAM MENINGKATKAN MUTU PEMBELAJARAN - Wahidin, Wahidin (STAI Sangatta Kutai Timur, 2024)
This research aims to describe the use of information technology-based learning media, the quality of learning at MAN Kapuas, and the application of information technology-based learning media in improving the quality of learning at MAN Kapuas. This type of research is descriptive-qualitative research. Data was obtained through observation, interviews, and documentation. The informants in this study were 11 people, consisting of 1 madrasa head, 1 deputy madrasa head for curriculum, 2 class X teachers, 2 class XI teachers, 2 class XII teachers, and 1 student each in his class. The results of the research show that the use of information technology-based learning media to improve the quality of learning at MAN Kapuas is considered successful. The quality of learning at MAN Kapuas increases through the use of information technology-based learning media at MAN Kapuas using the Animiz Animation Maker and Unity 3D applications while having discussions via the Quora application. The application of information technology-based learning media in improving the quality of learning at MAN Kapuas has been carried out well; this can be seen from the students being very motivated when learning using laptop/computer media, projectors/LCDs, internet networks, and speakers. Its use has an important role in improving the quality of student learning, including understanding the material being taught and increasing achievement outside the madrasah in the field of information technology and media applications. This research implies that teachers, in delivering learning material in class, must be clever in choosing the right media. Teachers must have creative and innovative ideas so that the learning atmosphere for students is more enthusiastic and motivated.